2017
DOI: 10.1148/radiol.2017161995
|View full text |Cite
|
Sign up to set email alerts
|

Hypertrabeculated Left Ventricular Myocardium in Relationship to Myocardial Function and Fibrosis: The Multi-Ethnic Study of Atherosclerosis

Abstract: Purpose:To determine if excess greater left ventricle (LV) trabeculation is associated with decreased average regional myocardial function, diffuse fibrosis, or both. Materials and Methods:This was a HIPAA-compliant institutional board approved multicenter study, and all participants provided written informed consent. Mean FD was 1.2 6 0.07 in both groups, and mean Ecc was 218.3 6 2.27 in the subjects who underwent FD and Ecc measurement. Global volumes and ejection fraction showed no differences between FD qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 29 publications
(24 reference statements)
1
12
2
Order By: Relevance
“…Unlike NC/C ratio, FD as a measure of LV trabeculation was associated with increased cardiac volumes and LV mass (more eccentric hypertrophy phenotype), but not LV concentricity. Although reduction in myocardial deformation has been shown in LVNC patients [ 36 39 ], our study demonstrated progressive impairment in regional circumferential strain with LV trabeculation extent even in healthy individuals. This was consistent with recent findings by Kawel et al [ 39 ], and we further demonstrated an impairment in diastolic relaxation with increased LV trabeculation in healthy subjects.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Unlike NC/C ratio, FD as a measure of LV trabeculation was associated with increased cardiac volumes and LV mass (more eccentric hypertrophy phenotype), but not LV concentricity. Although reduction in myocardial deformation has been shown in LVNC patients [ 36 39 ], our study demonstrated progressive impairment in regional circumferential strain with LV trabeculation extent even in healthy individuals. This was consistent with recent findings by Kawel et al [ 39 ], and we further demonstrated an impairment in diastolic relaxation with increased LV trabeculation in healthy subjects.…”
Section: Discussioncontrasting
confidence: 58%
“…Although reduction in myocardial deformation has been shown in LVNC patients [ 36 39 ], our study demonstrated progressive impairment in regional circumferential strain with LV trabeculation extent even in healthy individuals. This was consistent with recent findings by Kawel et al [ 39 ], and we further demonstrated an impairment in diastolic relaxation with increased LV trabeculation in healthy subjects. Of note, NC/C ratio lacked any associations with strain parameters, underscoring the limitations of NC/C ratio.…”
Section: Discussioncontrasting
confidence: 58%
“…Other researchers found similar results in pediatric patients and lower than normal GCS values in adult LVNC patients with good LV function as well [29,31]. However, decreased GCS and GRS values were also present in healthy participants with LV hypertrabeculation, and Cai et al described that higher global fractal dimension values were independently associated with decreased GCS after adjusting for age, sex and body mass index [32,33]. This result raises the question of whether the presence of LV hypertrabeculation causes this alteration or subclinical LV dysfunction is already present in LVNC patients regardless of having good LV function.…”
Section: Discussionmentioning
confidence: 66%
“…Only 6% of participants in the study had a maximum ratio .2.3 in more than 2 regions in an older age population (mean age of 68 years). 502,521 See Table 5 for diagnostic criteria for LVNC.…”
Section: Section 6 Future Directions and Research Recommendationsmentioning
confidence: 99%